A comparison of three different work to rest periods during intermittent sprint training on maintaining sprint effort performance - Timothy Rogers; Nicholas Gill; Christopher M. Beaven (Elsevier, 2024)
Background/objectives: Team sports are characterised by repeated maximal intensity bursts of activity, requiring significant energy contribution from the phosphagen pathways. The objective of this study was to evaluate the impact of different rest periods on repeated maximal intensity efforts. Methods: The effect of three different recovery periods (60 s, 90 s and 120 s) during a 10 × six-seconds intermittent sprint training protocol performed on a cycle ergometer was investigated. Thirteen part-time female athletes from two sports, Rugby Sevens and Netball competing for their state participated in the study. Peak Power (PPO), Mean Power (MPO), "total work" in the form of calorie expenditure, performance decrement, repetitions over 95% PPO, blood lactate, and RPE were recorded. Results: There was a significant effect of condition on MPO and calorie expenditure (p < 0.050). MPO was significantly lower for 60 s compared to 90 s (710.4 vs 734.4 W, ES = 0.27-0.42) and 120 s (710.4 vs 743.3 W, ES = 0.36-0.47). Calorie expenditure was significantly lower for 60 s compared to 90 s (4.41 vs 4.56 cal, ES = 0.25-0.46) and 120 s (4.41 vs 4.59 cal, ES = 0.40-0.48). There was a significant effect of time (60 s 11.7, 90 s 11.1.120 s 10.9 mmol/L, p < 0.010) but not condition (p = 0.617) for blood lactate accumulation, and a significant difference in session RPE between 60 and both 90 s and 120 s (60 s 15.5, 90 s 14.2. p = 0.034 120 s 13.9, p = 0.039). Conclusion: Shorter recovery durations resulted in decreased mean power and calorie expenditure, but higher RPE when compared to longer recovery periods. All three recovery periods may have fallen between the fast and slow phases of PCr resynthesis of approximately 20 and 180 s resulting in partial but not complete recovery. Total training time should be a consideration when determining what protocol to implement.